High school learning outcomes: The effect of self-regulation, resilience, and family environment - Amir Machmud; Irfan Alfaridzi Ramadhan (Jurnal Cakrawala Pendidikan, 2022)
Inspired by the poor Economics learning outcomes of students in state senior high schools (SSHS) in Cianjur regency, this study aims to determine and analyze self-regulation mediating the effect of resilience and family environment on student learning outcomes. It employed an explanatory survey with questionnaires and observations to collect the data. The population of this study comprises all grade XI social science students of SSHSs in Cianjur Regency, while the sample members selected randomly include 223 students. The data collected was then analyzed by using multiple linear regression analysis with the mediator variable. The results likely show that (i) resilience and family environment are in the high category, while self-regulation and learning outcomes are in the medium category. (ii) Both resilience and family environment influence self-regulation, and (iii) resilience, family environment, and self-regulation affect learning outcomes. (iv) Resilience affects learning outcomes either directly or indirectly through self-regulation. (v) Family environment likely influences learning outcomes directly or indirectly through self-regulation. The results of this study imply that the concepts of resilience, family environment, and self-regulation are relevant and can estimate student learning outcomes.